Gimap5 Inhibits Lung Cancer Growth by Interacting With M6PR - Dai, Pei; Tang, Zhongxiang; Ruan, Pinglang; Bajinka, Ousman; Liu, Dan; Tan, Yurong (Frontiers in Oncology, 2021)
Objective: Several studies have demonstrated the impacts of GTPases of immunity-associated proteins (GIMAPs) on malignant cells. However, the mechanisms through which Gimap5 regulates lung cancer cells are yet to be thoroughly investigated in the literature. Our study aimed to investigate the function of Gimap5 in the development of lung cancer. Methods: The expression levels of the GIMAP family were analyzed in lung cancer patients of various cancer databases and lung cancer cell lines. After the survival rates of the cells were analyzed, we constructed Gimap5 over-expressed lung cancer cell lines and assessed the effects of Gimap5 on cell migration, cell invasion, cell proliferation and the epithelial-mesenchymal transition (EMT). We later screened the interacting proteins of Gimap5 using Co-IP combined with mass spectrometry and then analyzed the expression and distribution of M6PR, including its impacts on protein-arginine deiminase type-4 (PADI4). Results: Findings indicated that GIMAP family expression decreased significantly in lung cancer cell lines. We also noticed that the downregulation of the GIMAP family was related to the poor prognosis of lung cancer patients. Our experimental results showed that Gimap5 could inhibit the migration, invasion, proliferation and EMT of lung cancer cell lines. Moreover, we found that Gimap5 promoted the transport of M6PR from the cytoplasm to the cell membrane, thereby inhibiting the enhancement of EMT-related PADI4. Conclusion: Our research suggested that Gimap5 could inhibit the growth of lung cancer by interacting with M6PR and that it could be a potential biomarker for the diagnosis and prognosis of lung cancer.